Broad-Spectrum Beta-Lactamases and Drug-Resistance Phenotypes of Enterobacteriaceae Isolated from Clinical Specimens in Gonbad-e Kavus, Golestan Province, Iran - Mohammad Hossein Akbari1; Ania Ahani Azari2; Leila Fozouni2 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: This study aimed to determine the frequency of extendedspectrum beta-lactamases (ESBL) and different drug resistance phenotypes in Enterobacteriaceae isolated from clinical specimens in Gonbad-e Kavus, Golestan Province. Methods: 220 clinical samples of urine, blood, pus, sputum, CSF, body fluids, and ear and eye discharge were collected during six months from April to September 2021 at a referral hospital. The samples were cultured on blood and MacConkey agar and incubated overnight at 37 °C. Standard biochemical tests and the API20E enteric identification system were used to identify bacteria. The Kirby-Bauer disk diffusion method determined the antibiotic resistance pattern, and the phenotypic confirmatory test was used for detecting ESBL producers. Results: 108 Enterobacteriaceae isolates were identified from different clinical specimens out of the samples. The isolates were Escherichia coli (36.1%), Klebsiella pneumonia (25%), Enterobacter cloacae (18.5%), Citrobacter freundii (11.1%) and Proteus mirabilis (9.2%). The highest resistance and susceptibility among the isolates belonged to sulfamethoxazole-trimethoprim (68.5%) and meropenem (11.1%), respectively. The highest prevalence of multidrug-resistant (MDR) and ESBL were observed in E. coli and Proteus mirabilis isolates. Conclusion: In this study, the high frequency of MDR phenotypes in the isolates may suggest an increasing trend of antibiotic resistance in Enterobacteriaceae. This could greatly impact the management and treatment of infections caused by these drug-resistant bacteria. Therefore, infection-control measures and continuous monitoring is recommended for controlling the spread of ESBL-producing strains in different geographical areas.